Blood-Based Biomarkers for Predictive Diagnosis of Cognitive Impairment in a Pakistani Population - Iqbal, Ghazala; Braidy, Nady; Ahmed, Touqeer (Frontiers in Aging Neuroscience, 2020)
Numerous studies have identified association between age-related cognitive impairment (CI) and oxidative damage, accumulation of metals, amyloid levels, tau and deranged lipid profile. There is a concerted effort to establish reliability of these blood based biomarkers for predictive diagnosis of CI and its progression. We assessed the serum levels of high density lipoprotein (HDL) cholesterol, low density lipoprotein (LDL) cholesterol, triglycerides, total cholesterol, selected metals (Cu, Al, Zn, Pb, Mn, Cad), and total-tau and amyloid beta-42 protein in mild (n=71), moderate (n=86) and severe (n=25) cognitively impaired patients and compared them with age-matched healthy controls (n=90)from Pakistan. We found that a decrease in HDL cholesterol (correlation coefficient r=0.467) and amyloid beta-42 (r=0.451) were associated with increase severity of CI. On the other hand, an increase in cholesterol ratio (r= -0.562), LDL cholesterol (r= -0.428), triglycerides and total-tau (r= -0.443) were associated with increased severity of CI. Increases in cholesterol ratio showed the strongest association and correlated with increases in tau concentration (r=0.368), and increased triglycerides were associated with decreased amyloid beta-42 (r= -0.345). Increased Cu levels showed the strongest association with tau increase and increased Zn and Pb levels showed the strongest association with reduced amyloid beta-42 levels. Receiver Operating Characteristic (ROC) showed the cutoff values of blood metals (Al, Pb, Cu, Cad, Zn and Mn), total-tau and amyloid beta-42 with sensitivity and specificity. Our data shows for the first time that blood lipids, metals (particularly Cu, Zn, Pb and Al), serum amyloid beta-42/tau proteins modulate each other’s levels and can be collectively used as a predictive marker for CI.